What determines patient preferences for treating low risk basal cell carcinoma when comparing surgery vs imiquimod?: a discrete choice experiment survey from the SINS trial - Tinelli, Michela; Ozolins, Mara; Bath-Hextall, Fiona; Williams, Hywel C. (BioMed Central, 2012)
Background: The SINS trial (Controlled Clinical Trials ISRCTN48755084; Eudract No. 2004-004506-24) is a randomised controlled trial evaluating long term success of excisional surgery vs. imiquimod 5% cream for low risk nodular and superficial basal cell carcinoma (BCC). The trial included a discrete choice experiment questionnaire to explore patient preferences of a cream versus surgery for the treatment of their skin cancer. Methods: The self-completed questionnaire was administered at baseline to 183 participants, measuring patients’ strength of preferences when choosing either alternative ‘surgery’ or ‘imiquimod cream’ instead of a fixed ‘current situation’ option (of surgical excision as standard practice in UK). The treatments were described according to: cost, chance of complete clearance, side effects and appearance. Participants had to choose between various scenarios. Analysis was performed using a mixed logit model, which took into account the impact of previous BCC treatment and sample preference variability. Results: The analysis showed that respondents preferred ‘imiquimod cream’ to their ‘current situation’ or ‘surgery’, regardless of previous experience of BCC symptoms and treatment. Respondents were more likely to be worried about their cosmetic outcomes and side effects they might experience over and above their chance of clearance and cost. Those with no experience of surgery (compared with experience) valued more the choice of ‘imiquimod cream’ (£1013 vs £781). All treatment characteristics were significant determinants of treatment choice, and there was significant variability in the population preferences for all of them. Conclusions: Patients with BCC valued more ‘imiquimod cream’ than alternative ‘surgery’ options, and all treatment characteristics were important for their choice of care. Understanding how people with a BCC value alternative interventions may better inform the development of health care interventions.